Measuring service quality and customer satisfaction: the case study of Asajaya District Office / Nazatul Fazirah Mori - Mori, Nazatul Fazirah (2013)
Services is the intangible products that company offered such as accounting, banking, cleaning, consultancy, education, insurance, expertise, medical treatment, or transportation. Sometimes services are difficult to identify because they are closely associated with goods like the combination of a diagnosis with the administration of a medicine. No transfer of possession or ownership takes place when services are sold, and they cannot be stored or transported, is instantly perishable, and come into existence at the time they are bought and consumed.